3.2 What Are the Intrapartum Risks Associated with Obesity in Healthy Women Without Additional Risk Factors? Evidence from the Birthplace in England National Prospective Cohort Study. (26th April 2013) - Hollowell, J; Pillas, D; Rowe, R; Linsell, L; Knight, M; Brocklehurst, P
Abstract : Maternal obesity is a risk factor for intrapartum complications but some risks may be attributable to the higher prevalence of co-morbidities. This study evaluated the impact of maternal obesity on outcomes requiring obstetric or neonatal care in otherwise low risk births. Methods: We analysed 17, 230 women without additional risk factors planning obstetric unit birth in the Birthplace cohort. We adjusted for maternal characteristics using Poisson regression. We evaluated two composite outcomes capturing need for obstetric or neonatal care. Results: The risk of requiring obstetric care (augmentation, instrumental/emergency caesarean delivery, blood transfusion, 3rd/4th degree tear, high dependency care) tended to increase with BMI, but nulliparous women of normal weight had higher absolute risks and were more likely to require obstetric care than multiparous women of BMI > 35 kg/m2. The perinatal composite (intrapartum stillbirth, early neonatal death or neonatal unit admission) exhibited a similar pattern: absolute perinatal risks were higher in nulliparous women of normal weight vs. multiparous women with BMI > 35 kg/m 2 (3.7% vs. 2.9%). Conclusions: Otherwise healthy obese multiparous women have lower intrapartum risks than nulliparous women of normal weight. Planned birth in Alongside Midwifery Units may be safe for some multiparous women with BMI > 35 kg/m2.